Trends and Future Research in Corporate Governance: A Bibliometric Analysis (2014-2024) - Kurnia, Lusi; Saifi, Muhammad; Damayanti, Cacik Rut (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
This study aims to elucidate current trends in corporate governance literature through a bibliometric analysis of papers published in Scopus from 2014 to 2024, encompassing 577 selected articles. Employing VOSviewer and R Studio, the analysis provides a comprehensive overview of publication trends, thematic evolution, and key contributors across three distinct time periods. The study reveals significant keywords like audit committee, board of directors, and corporate social responsibility, emphasizing the scrutiny of corporate governance mechanisms and codes. Clusters delve into governance management systems, such as board composition and audit quality, offering insights into firm performance and new code exploration. These clusters serve as valuable resources for future research, guiding investigations, and advancing knowledge in corporate governance. Additionally, the thematic evolution of trends over the past decade underscores the dynamic nature of research interests, informing scholars’ agendas and contributing to the field’s advancement. This study holds significant implications for academia, practitioners, and policymakers in corporate governance.